PENGARUH RELIGIUSITAS, SERTIFIKASI HALAL, DAN BAHAN PRODUK TERHADAP KEPUTUSAN PEMBELIAN - Wawan Wasik Marzuki; Triyono Triyono (Universitas Muhammadiyah Semarang, 2021)
The purchasing decision is influenced by several aspects. In this research,the writer will discuss about the influence of religiosity, halal certification andproduct ingredients. In this study, the population used was consumers of DokiDoki Streetfoodproducts in Semarang City during the event and because the population wasunknown, the sampling technique used was to use the Lemeshow formula whichresulted in 100 respondents.This research is a quantitative research and uses incidental sampling,namely the technique of determining the sample based on chance, that is, anyonewho happens to meet the researcher and can be used as a sample if it is consideredthat someone who happens to be met is suitable as a data source. The results showsthat Religiosity, Halal Certification, Product Ingredients have positive effect onPurchasing Decisions, both pratially and simultanously.